MOTIVASI ANAK PETANI MENJAID PETANI - Prawesti Nooring (Agro Ekonomi, 2010)
One of the  reason why the land function  of rice field keep changing was because farmer’s child lost their interest in continuing their parent’s agricultural business. This research was purposed to know the motivational level of farmer’s child motivation to be a farmer in Ngaglik sub district Sleman Regency. The basic method in this research was analytical descriptive  method. Samples were taken from 6 villages in Ngaglik Sub district. Sample consist of 60 people which  taken by using stratified random sampling method, based on their home distance to the district main road ( north ring road and Kaliurang street). In every villag were taken 5 samples  who has longer distance and 5 others has shorter distance home location to the main road. Data was analyzed by proportion test and multiple regression test. The result of this research showed that only 26,67% farmer’s child has high motivation to be a farmer. Attitude and understanding was a significant factor that  influences farmer’s child motivation to be a farmer. Age, educational level, perception, working opportunities, parent’s role, the local authority officer’s role, and home location distance, were not significant factors that affect farmer’s child motivation to be a farmer.